Global root trait underrepresentation in Paleotropical communities: a qualitative analysis - Lee, Ming Yang; Andersen, Kelly M. (Frontiers in Forests and Global Change, 2023)
Many ecosystem processes revolve around plant roots and the rhizosphere, but root trait knowledge has generally lagged behind aboveground plant traits from leaves and stems. In particular, root trait representation of Paleotropical species and tropical communities in modern trait databases remains poor, constraining our understanding of belowground processes in these regions. Therefore, we sought to examine the current state of root trait representation and associated topics in the Paleotropics to identify gaps and biases in the existing literature. Using an exhaustive literature scan, we compiled a list of publications that contained various belowground trait information.Subsequently, we utilised a statistical topic modelling method to analyse abstracts of publications in order to identify topics studied alongside root trait documentation. Finally, we consolidated trends in root trait coverage and topics across five geographical regions and four time periods to illustrate shifts in literature and knowledge of ecological processes revolving around roots. Root trait representation was heavily biased towards root biomass but other aspects of root systems such as physiology, architecture and anatomical traits remain underrepresented. We categorised 23 unique topics around root trait literature across eight categories: ecosystem productivity and biomass stocks, plant functional traits, resource availability, ecosystem processes and dynamics, mycorrhizal colonisation, edaphic processes, seedling experiments, and global change and variation. Traits and topic coverage were unequally distributed across the Paletropics and exhibited a notable shift in focus from resource limitation and mycorrhizae research to root trait variation at large spatial and temporal scales over the last 50 years of root trait literature. Given these trends and the heterogenous effects global change exerts on the tropics at a regional scale, we provided several recommendations to This is a provisional file, not the final typeset article facilitate inter-study comparisons of traits to advance the field's understanding of belowground ecosystem processes in pantropical communities.